Inhibition of CYP3A4 and CYP1A2 by Aegle marmelos and its constituents. (1st February 2016) - Manda, Vamshi K.; Avula, Bharathi; Chittiboyina, Amar G.; Khan, Ikhlas A.; Walker, Larry A.; Khan, Shabana I.
Abstract: 1.  Aegle marmelos (bael) is a popular tree in India and other Southeast Asian countries. The fruit is usually consumed as dried, fresh or juice, and is reported to have a high nutritional value and many perceived health benefits. Despite its edible nature and therapeutic properties, no studies are reported regarding its effects on major drug metabolizing enzymes. 2. This study was aimed to evaluate the inhibitory potential of methanolic extract of A. marmelos fruit and its constituents (three furanocoumarins, namely marmelosin, marmesinin and 8-hydroxypsoralen, and 1 alkaloid, aegeline) towards major Cytochrome P450 enzymes (CYP3A4, 2D6, 1A2, 2C9 and 2C19) using human liver microsomes and recombinant CYPs. 3. The methanolic extract and marmelosin was found to be competitive and time-dependant inhibitor of CYP3A4. While reversible and non-competitive inhibition was observed for CYP1A2. Time-dependent inhibition of CYP3A4 was not affected by the addition of reduced glutathione. Marmesinin showed moderate inhibition of CYP3A4 and 1A2, while aegeline was a very weak inhibitor of CYP3A4 and showed no inhibition for CYP1A2 isoform. No significant inhibition of recombinant CYP2D6, 2C9, and 2C19 was seen with the extract or its constituents. 4. This is the first report of CYP3A4 and CYP1A2 inhibition by A. marmelos extract and one of its furanocoumarins, marmelosin. Further studies are warranted to determine if acute or prolonged use of bael fruit could affect the pharmacokinetics of drugs that are substrates of CYP3A4 or CYP1A2.